Необычное поведение муравьев при сахарной съемке летом 2015 года - Gilyov, A. V.; Gilyova, O. B.; Гилёв, А. В.; Гилёва, О. Б. (Tyumen State University Herald. Natural Resource Use and Ecology, 2017)
Accounting for carbohydrate baits («sugar shooting») is a method widely used to study various aspects of the ants biology. In the summer of 2015, we studied the visit activity and the behavior of ants of different species with the use of carbohydrate baits in the taiga biocenoses of the Middle Urals. A phenomenon of rejecting the carbohydrate baits by workers of several species of ants was discovered. In total, 11 species of ants of 5 genera declined sugar syrup: Formica aquilonia, F. rufa, F. pratensis, F. fusca, F. rufibarbis, F. exsecta, Lasius niger, Myrmica rubra, M. ruginodis, Leptothorax acervorum, Tetramorium caespitum. At the same time, the activity of working individuals of all kinds was high, the red forest ants continued to visit the colonies of aphids. The refusal of sugar syrup was observed from the middle of August until the end of the season. The phenomenon was clearly local in nature, in other places all kinds of ants actively visited carbohydrate baits. In the summer of 2016, no carbohydrate baits were observed. The cause of this phenomenon could be the unfavorable weather conditions in 2015, combined with some local factors that affected the course of certain stages of the seasonal cycle in ants and caused a corresponding change in food preferences. The presence of space-time variations in food preferences in ants should be taken into account when carrying out the calculations on carbohydrate baits. Учеты на углеводных приманках («сахарная съемка») – метод, широко применяемый для изучения различных сторон биологии муравьев. Летом 2015 г. изучали активность посещения и поведение муравьев разных видов на углеводных приманках в таежных биоценозах Среднего Урала. Обнаружено не описанное ранее явление отказа от посещения углеводных приманок рабочими нескольких видов муравьев. Всего от сахарного сиропа отказались 11 видов муравьев 5 родов: Formica aquilonia, F. rufa, F. pratensis, F. fusca, F. rufibarbis, F. exsecta, Lasius niger, Myrmica rubra, M. ruginodis, Leptothorax acervorum, Tetramorium ...